Основные этапы и тенденции трансформации украинского общества: от перестройки до "оранжевой революции" - Головаха, Е.; Панина, Н. (Социология: теория, методы, маркетинг, 2006)
The article deals with the analysis of main stages and tendencies of social trans formations that have been taken place in Ukraine since the wellknown Perestroika in the ex-USSR. Transformational processes are studied in very important for Ukrainian society aspects, such as: institutional, sociostructural, and sociopsychological. Besides, the authors concentrated a special attention on the role of classes, elites, and the broad masses in the different stages of period have been analyzed.